Epigenetic Modifications and Therapy in Uveitis - Zou, Yanli; Li, Jing Jing; Xue, Wei; Kong, Xiangbin; Duan, Hucheng; Li, Yiqun; Wei, Lai (Frontiers in Cell and Developmental Biology, 2021)
Uveitis is a sight-threatening intraocular inflammation, and the exact pathogenesis of uveitis is not yet clear. Recent studies, including multiple genome-wide association studies (GWASs), have identified genetic variations associated with the onset and progression of different types of uveitis, such as Vogt–Koyanagi–Harada (VKH) disease and Behcet’s disease (BD). However, epigenetic regulation has been shown to play key roles in the immunoregulation of uveitis, and epigenetic therapies are promising treatments for intraocular inflammation. In this review, we summarize recent advances in identifying epigenetic programs that cooperate with the physiology of intraocular immune responses and the pathology of intraocular inflammation. These attempts to understand the epigenetic mechanisms of uveitis may provide hope for the future development of epigenetic therapies for these devastating intraocular inflammatory conditions.